2019
DOI: 10.1590/s2175-97902019000100249
|View full text |Cite
|
Sign up to set email alerts
|

Anticonvulsant evaluation of 2-pyrazolines carrying naphthyl moiety: An insight into synthesis and molecular docking study

Abstract: A series of N-substituted-3-(napthalen-2-yl)-5-substituted phenyl-4,5-dihydropyrazole-1-carbothioamide derivatives (4a-n) were synthesized with the view of structural requirements of pharmacophore for potential anticonvulsant agents. The synthesized compounds were assayed intraperitoneally (i.p.) and subcutaneously (s.c.) in mice against seizures induced by MES and scPTZ methods, respectively. Neurologic deficit was evaluated by rotarod method. Among the tested compounds, 4g, 4i, 4j and 4n emerged as the most … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…Miscellaneous N-substituted-3-(naphthalene-2-yl)-5-substituted phenyl-4,5-dihydro pyrazole-1-carbothioamide derivatives (154) possessed good anticonvulsant activity against the MES model at 30 mg/kg at the period of 0.5 h indicating their good ability to prevent seizure spread. [71] Fluoropyrazole-sulfonylurea and thiourea derivatives (155,156) have antidiabetic potential. However, a marked resumption in the hypoglycemic activity was seen in compounds after the cyclization of the thiourea group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Miscellaneous N-substituted-3-(naphthalene-2-yl)-5-substituted phenyl-4,5-dihydro pyrazole-1-carbothioamide derivatives (154) possessed good anticonvulsant activity against the MES model at 30 mg/kg at the period of 0.5 h indicating their good ability to prevent seizure spread. [71] Fluoropyrazole-sulfonylurea and thiourea derivatives (155,156) have antidiabetic potential. However, a marked resumption in the hypoglycemic activity was seen in compounds after the cyclization of the thiourea group.…”
Section: Discussionmentioning
confidence: 99%
“…N ‐substituted‐3‐(naphthalene‐2‐yl)‐5‐substituted phenyl‐4,5‐dihydro pyrazole‐ 1‐carbothioamide derivatives ( 154 ) possessed good anticonvulsant activity against the MES model at 30 mg/kg at the period of 0.5 h indicating their good ability to prevent seizure spread [71] . Fluoropyrazole‐ sulfonylurea and thiourea derivatives ( 155 , 156 ) have antidiabetic potential.…”
Section: Biological Activities Of Pyrazoline Derivativesmentioning
confidence: 99%
“…Epilepsy is as a collective termfor brain function disorders that are characterized by periodic and unpredictable occurrence of seizures. The molecular docking study compound was carried out in order to assess their interaction and binding modes with target receptor and good biological activity using auto dock software [1] . We have docked the compounds in Autodock Vina docking software.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have reported considerable biological activities when substitution occurs at position 1-, 3- and 5- of the pyrazoline ( Figure 1 ), such as anticonvulsant, antimalarial [ 2 ], anti-cardiovascular [ 3 ], anticancer [ 4 ], anti-amoebic [ 5 ], antimicrobial [ 6 , 7 ] and anti-tumor activities [ 8 ]. Meanwhile, carbothioamide derivatives were found to have significant pharmacological activities, such as monoamine oxidase (MAO) inhibitors [ 9 , 10 ], antituberculosis [ 11 , 12 , 13 ] and anticonvulsant activities [ 14 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%